Arbeiten mit Funktionsgraphen – Zur Diagnose von Fehlern und Fehlvorstellungen beim Funktionalen Denken (mathematica didactica, 2021)
Functional thinking and in particular the interpretation and construction of graphs of functions holds a variety of potential difficulties. When learners work with graphs, errors and misconceptions can often be identified. In order to foster functional thinking teachers need the ability to diagnose individual preconditions and needs of learners. The present study reveals that preservice mathematic teachers can diagnose only a few of these errors and misconceptions at the beginning of their studies, despite the previous discussion of the underlying theoretical content during a lecture. Moreover, their diagnoses are usually superficial at first. By means of an intervention with authentic videos, a small improvement in the preservice teachers' diagnostic performance could be achieved.